Variation of Nutrient Content in Different Irish Potato Varieties with Storage Time in Kabale District. - Nshimyimana, Evarist (Kabale University, 2024)
This study investigated the variation of Irish potato nutrients with storage time in Kabale municipality, kabale district. Two Irish potato varieties were selected based on common Irish potatoes grown in the area. 20 Irish potatoes from stems of two different varieties were collected from a garden. Four of the fresh Irish potatoes were peeled on arrival in the laboratory immediately. One piece of about 100g was cut from the peeled Irish potatoes and then pounded in the motor, 100ml of water was added to the products to obtain the potato extract. This was filtered the concentration of reducing sugars was determined using Benedict's solution by titration method. The same was done for the remaining 12 Irish potatoes for every two weeks. The concentration of vitamin C in each of the Irish potato extracts was· determined by redox titration of the extracts with standard acidified potassium iodate solution in the presence of potassium iodide using starch indicator. The study found out that the concentration of vitamin C reduced with storage time while the concentration of reducing sugars increased with storage time maybe because, towards germination, starch was being changed to reducing sugars.